What Explains Educational Disparities in Older Adults’ Propensity to Work? (Journal of Organizational Psychology, 2017)
Although older Americans’ employment has surged over the last 20 years, less-educated adults are much less likely to work at older ages than their better-educated counterparts. Using data from the Health and Retirement Study linked to job demands information derived from the Occupational Information Network, this study identifies those factors driving educational differences in old-age employment. The results show that self-reported health and work-restricting health conditions account for almost half of the employment gap. Job demands and other job characteristics, including the presence of difficult working conditions, also account for a significant share of the gap.
Keywords: Organizational Psychology; Educational Disparities